HOW TO USE SMART FINGERS TECHNIQUE IN TEACHING ENGLISH TENSES - Ade Sudirman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This article informs how to use Smart Fingers technique in teaching English tenses. The Smart Fingers technique is a new teaching English tenses technique which will help teachers or students to learn and master 16 English tenses fast due to its simplicity in its implementing. Meanwhile, tense itself is a part of grammar material that is often avoided by several English learners as it is very complicated lesson. In fact, English sentences used in daily activity and especially academic field consist of tenses. Thus, smart fingers technique becomes an alternative technique to overcome that problem. The use of this technique is so simple, just need fingers of hands. This article also discusses the kinds, functions of Smart Fingers and their achievement indicators. There are five kinds of Smart Fingers technique, namely Smart Fingers (SF) ”Memorizing Tenses”, SF “Naming Tenses”, SF “Auxiliary Verbs”, SF “Verbs vs To Be”, SF “Smart Short Tenses”. Each kind of Smart Fingers technique has different functions and achievement indicators.